25th IAEA Fusion Energy Conference: summary of sessions EX/S, EX/W and ICC. (5th October 2015) - Sen, A.
Abstract: This paper provides a summary overview, based on papers presented at the 25th IAEA Fusion Energy Conference (FEC), in the area of magnetic confinement experiments related to stability (EX/S), wave–plasma interactions, current drive, heating, energetic particles (EX/W) and innovative confinement concepts (ICCs). A selection of results that represent progress made since the last FEC in a few important thematic areas that are relevant for the successful and safe operation of future fusion devices like ITER, is highlighted.